Hubungan Pengetahuan Ibu Hamil Sebelum dan Setelah Edukasi Prenatal Yoga di UPT Puskesmas Pal III Pontianak - Lina Astuty; Youlenta Ernesontha; Trivina Trivina; Agnes Dwiana Widi Astuti; Susanna Susanna (JURNAL BIDANG ILMU KESEHATAN, 2026)
Background: Physiological changes in pregnant women begin in the first trimester and reach their peak during labor. These changes are generally well tolerated by healthy women; however, they may worsen or trigger pre-existing medical conditions (Yulizawati et al., 2017). Prenatal yoga is a modified form of yoga specifically designed to accommodate the physical needs and conditions of pregnant women, aiming to prepare them physically, mentally, and spiritually for childbirth. Based on the records of antenatal care visits at Pal III Community Health Center, Pontianak, a total of 114 pregnant women attended from November 2025 to January 2026. Common pregnancy-related discomforts, such as anxiety, back pain, and fatigue, motivated the researchers to provide prenatal yoga education to pregnant women. Objective: This study aimed to assess the knowledge of pregnant women before and after receiving prenatal yoga education at Pal III Community Health Center, Pontianak. Methods: This study employed a quantitative descriptive design with a cross-sectional approach. The research was conducted from April 9 to April 16, 2025. A total of 30 pregnant women participated as the study sample. Results: The findings indicated that before receiving prenatal yoga education, the majority of respondents (18 participants; 60%) had a moderate level of knowledge regarding prenatal yoga. After the educational intervention, most respondents (22 participants; 73%) demonstrated a good level of knowledge. Improvements in knowledge were influenced by several factors, including educational level, occupation, and age. Conclusion: The knowledge of pregnant women regarding prenatal yoga before the educational intervention was generally categorized as moderate, with 60% of the 30 respondents falling into this category. Following the educational intervention, the participants' knowledge improved, with 73% of the same respondents demonstrating a good level of knowledge. These findings suggest that prenatal yoga education effectively enhances pregnant women's knowledge about prenatal yoga.